2014
DOI: 10.1002/jcp.24619
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Adipogenesis and Insulin Resistance in Epicardial Fat-Mesenchymal Cells From Patients With Cardiovascular Disease

Abstract: The thickness of epicardial adipose tissue (EAT), which is an inflammatory source for coronary artery disease (CAD), correlates with insulin resistance. One trigger factor is impaired adipogenesis. Here, our aim was to clarify the underlying mechanisms of insulin resistance on EAT-mesenchymal cells (MC). EAT and subcutaneous adipose tissue (SAT) were collected from 19 patients who were undergoing heart surgery. Their dedifferentiated adipocytes (DAs) and/or MCs were cultured. After the induction of adipogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
2
25
0
2
Order By: Relevance
“…An interesting result of our study is the significant correlation between EAT and HOMA-IR, consistent with the reported data in adults (53,54) and in contrast with the results of those few pediatric studies available (50,55). In pediatric cohorts, despite not finding an association between EAT and HOMA-IR, EAT was able to identify patients with insulin resistance (19,51).…”
Section: Eat Evaluationsupporting
confidence: 91%
“…An interesting result of our study is the significant correlation between EAT and HOMA-IR, consistent with the reported data in adults (53,54) and in contrast with the results of those few pediatric studies available (50,55). In pediatric cohorts, despite not finding an association between EAT and HOMA-IR, EAT was able to identify patients with insulin resistance (19,51).…”
Section: Eat Evaluationsupporting
confidence: 91%
“…Previous studies found that pericardial fat is associated with atrial conduction [24,25] and EAT is associated with blood pressure levels [26], AF [27] and cardiovascular disease [18,20,28,29]. Van Gaal et al showed that EAT is a biologically active organ that may play a role in the association between obesity and CAD [30].…”
Section: Discussionmentioning
confidence: 99%
“…(1) demuestra que existe una fuerte asociación entre el tejido adiposo abdominal y corporal con el tejido adiposo epicárdico medido por ecocardiografía en mujeres posmenopáusicas. Se ha observado que la grasa epicárdica de las mujeres produce mayores concentraciones de leptina que la de los varones (5,15,16). Actualmente se está estudiando la relación de esta citocina con el riesgo cardiovascular (5,15,16), planteándose si es la precursora de la obesidad y la diabetes, así como de la disminución de la distensibilidad arterial.…”
Section: Discussionunclassified
“…Así, al igual que en otros estudios (14,16), la GV mostró una sensibilidad y una especificidad ligeramente mayor que el resto de parámetros estudiados. No obstante, en el estudio de Ozhan y cols.…”
Section: Figuraunclassified